2018
DOI: 10.1111/fme.12274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ageing accuracy with complementary non‐lethal methods for slow‐growing, northern populations of shoal bass

Abstract: In the upper Chattahoochee River basin, where some populations of shoal bass, Micropterus cataractae Williams & Burgess, are imperilled, age and growth data are lacking. Age and growth of shoal bass in this basin were assessed with non‐lethal means using scales and mark–recapture. Mark–recapture data allowed for estimation of accuracy and determination of effects of any scale‐based inaccuracies on growth models. Scale‐based age estimates were accurate for 57% of the samples, and errors of 1 to 3 years included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…However, their growth model failed to exhibit an asymptote, in part because of the maximum age of 12 found in that population (Long et al. 2018). For Smallmouth Buffalo in our study, which lived to 61 years, a clear asymptote is apparent in the scatterplot of TL against estimated age for all structures we examined, suggesting that inaccurate and imprecise age data from other structures, such as nonlethal pectoral fin rays, may be useful for growth modeling, at least for comparison purposes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, their growth model failed to exhibit an asymptote, in part because of the maximum age of 12 found in that population (Long et al. 2018). For Smallmouth Buffalo in our study, which lived to 61 years, a clear asymptote is apparent in the scatterplot of TL against estimated age for all structures we examined, suggesting that inaccurate and imprecise age data from other structures, such as nonlethal pectoral fin rays, may be useful for growth modeling, at least for comparison purposes.…”
Section: Discussionmentioning
confidence: 98%
“…We found that Smallmouth Buffalo exhibited slow growth after approximately 20 years and longevity up to 61 years, suggesting that growth analyses may be sufficient with imprecise and inaccurate age estimates in the range we found. For example, Long et al (2018) used nonlethal scales, which are imprecise and inaccurate, to estimate age in conjunction with mark-recapture to measure growth for Shoal Bass Micropterus cataractae and found growth models to diverge only for the youngest and oldest individuals in the population. Moreover, their models were sufficient to compare to other populations and discern fast-growing from slow-growing populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation